1836 Tenn. Comp. Stat. 100, Arms, 1825-Chapter 19, § 1 - (:unkn) unknown (My University, 1825)
§When any sheriff, coroner, or constable, shall know of his own knowledge, or upon the representation of any person, or if he or they, shall have good reason to suspect, any person of being armed with the intention of committing a riot or affray, or the wounding or killing any person, it shall be the duty of all such officers, immediately to arrest all such persons so suspected, and return them before some justice of the peace, whose duty it shall be, upon proof being made, that there was reasonable ground to suspect such person or persons for being armed, with intent to disturb or commit a breach of the peace, to bind such person or persons in a bond with two or more good and sufficient securities, in a sum of not less than two hundred and fifty dollars, and not exceeding two thousand dollars, conditioned for his or their good behavior and peaceable deportment for the term of twelve months thereafter
Keywords: GOING ARMED